ANALISIS KINERJA PERPAJAKAN DAERAH DI KOTA MEDAN - Dede Ruslan (Quantitative Economics Journal, 2016)
Delegation of authority taxation (tax assignment) was good to regional governments tend to date still lacks clear standards and universal. Tax assignment and restructuring of taxes and levies in a sustainable course can only be done by revising Law No. 28 of 2009 which is the basis in the management of local taxes and levies. How the performance of local taxationin Medan running has been the material of interest to be studied. Assessment approach used in this study diguankan kualitaitif research and quantitative research. Whereas in other research used to obtain a quantitative description on the contributions and the rate of development of local taxes to the local tax revenue and the performance of Medan, through analytical tools tax elasticity, tax ratio and TPI. The results showed that the performance of local taxes through tax elasticity is known that the average percentage change in local taxes to the percentage change in the GDP amounted to 1.99%, while the ratio of the tax does not show improvement every year. Tax ratio that existed during the period 2011-2015 ranged from 0.62% to 0.85%. For the effectiveness of the tax is relatively stable with average at 0.79 and when viewed from the level of efficiency since the year 2011 to 2015 ranged from 0% to 2.15%. In an average rate of 0.04% CCER only. These values were lower and included in the category of good.